DEVELOPING PERSONALIZED LEARNING TECHNOLOGIES IN LOWER-SECONDARY ENGLISH LANGUAGE TEACHING IN UZBEKISTAN: A CONTEXTUALIZED MODEL AND EVALUATION FRAMEWORK - Hojiyeva Maftuna Ulug‘bekovna (Bright Mind Publishing, 2026)
Personalized learning (PL) is increasingly positioned as a practical pathway for improving learner engagement and achievement by tailoring content, pacing, and learning routes to individual needs. In English language teaching (ELT), PL is especially relevant because learners enter classrooms with heterogeneous proficiency levels, motivational profiles, and access to learning resources. This article develops a contextualized PL model for lower-secondary ELT in Uzbekistan and proposes an evaluation framework aligned with national education reforms and foreign language policy priorities. Drawing on research in differentiated instruction, formative assessment, learner autonomy and motivation, and blended learning, the model integrates (i) learner profiling (diagnostics and ongoing evidence from learning tasks), (ii) flexible learning pathways (choice, tiered tasks, station rotation, and optional digital supports), (iii) feedback-rich assessment (rubrics, portfolios, and reflection), and (iv) teacher facilitation supported by focused professional learning. The evaluation design follows a quasi-experimental logic complemented by qualitative implementation evidence (classroom observation, learner questionnaires, and portfolio artifacts) in grades 5–6 across general secondary schools in Jizzakh and Andijan regions and Tashkent city. By articulating implementable components and measurable indicators, the paper offers a locally relevant framework for PL in ELT that can guide pilot implementations and dissertation-level research while highlighting constraints such as classroom management shifts, teacher role transformation, and equitable access to learning resources.
Keywords: Personalized learning; English language teaching; lower-secondary education; Uzbekistan; differentiated instruction; formative assessment; blended learning; learner autonomy.